Resurrecting the Brother of Jesus : The James Ossuary Controversy and the Quest for Religious Relics - McNary-Zak, Bernadette; Byrne, Ryan (Book collections on Project MUSE., 2009)
This collection of essays explores the circumstances of an archaeological hoax in which a box of skeletal remains was passed off as belonging to James, the brother of Jesus. Contributors discuss the role of media sensationalism, the use and misuse of religion, and the responsibilities of scholars as public interpreters of discoveries with religious significance.